Discovery of brand image by the arts: Empirical comparison of Arts-Based Brand Research Methods (ABBR) - Carsten Baumgarth; Özlem Yildiz (Hochschule für Wirtschaft und Recht Berlin, IMB Institute of Management Berlin, 2016)
This work develops an evaluation framework to Arts-Based Brand Research (ABBR) to make methods comparable. Further the evaluation framework is used to compare four arts-based methods. It turned out that previous studies try to capture the brand image on a verbal cognitive level, but this proceeds cannot detect the unconscious emotions and attributes. There is a risk of standardized survey, because the emotions and attributes to the brand, which manifest themselves through images, colors, fragrances, etc., cannot be detected. The reason is the loss between the "translations" of non-verbal in the verbal attributes. Therefore, there are arts-based methods that allow working closely on the human senses. Four methods were compared based on the evaluation framework: Lego Serious Play (LSP), Multi Sensory Sculpting (MSS), Psychodrawing (PD) and Collage (C). The results of this study show that the newly developed evaluation framework allows a distinguished and systematic comparison of market research methods. The evaluation framework led to the conclusion that art-based methods are well suited even on sensitive issues such as sustainability. Futhermore the respondents felt the methods as entertaining and enjoyable. The Methods Collage and Psychodrawing performed particularly well with respect to the required time and the variety of associations. – – Diese Arbeit entwickelt ein konzeptionelles Beurteilungsraster, um Arts-Based Brand Research (ABBR) Methoden zu beurteilen. Dieses wurde dann genutzt, um vier kunstbasierte Methoden miteinander zu vergleichen. Es stellte sich heraus, dass bisherige Untersuchungen versuchen, das Markenimage, das unter anderem aus unbewussten Emotionen und Attributen besteht, auf verbal- kognitiver Ebene zu erfassen. Es besteht die Gefahr, dass bei einer standardisierten Befragung der Konsumenten die Emotionen und Attribute zur Marke, die sich durch Bilder, Farben, Düfte usw. im Kopf manifestieren, nicht erfasst werden können, da bei der "Übersetzung" von Nonverbalem in das Verbale Attribute verloren gehen. Deshalb existieren kunstbasierte Methoden, die zulassen, nah an den menschlichen Sinnen zu arbeiten. Es wurden vier Methoden anhand des Beurteilungsrasters miteinander verglichen: Lego Serious Play (LSP), Multi Sensory Sculpting (MSS), Psychodrawing (PD) und Collagen-Technik (C). Die Ergebnisse dieser Studie zeigen, dass das neu entwickelte konzeptionelle Beurteilungsraster eine gute und systematische Vergleichbarkeit von Marktforschungsmethoden zulässt. Diese ließ den Schluss zu, dass kunstbasierte Methoden auch bei sensiblen Themen, wie der Nachhaltigkeit, gut einsetzbar sind und die Befragten die Methoden als sehr angenehm und kurzweilig empfanden. Besonders gut schnitten die Methoden Collage und Psychodrawing in Bezug auf die benötigte Zeit und die Vielfalt der Assoziationen ab.
Keywords: 650; Marktforschung; Kunst; Markenführung; Markenimage; Wahrnehmung; Werbepsychologie